Perspectives on the effectiveness of green buildings in climate change mitigation: a study of the City of Johannesburg - Makgalemele, Malesotse Cecilia (My University, 2021)
It has been proved that anthropogenic activities globally have resulted in accelerated climate change and global warming, beginning with the industrial revolution, through the release of greenhouse gases of which Carbon Dioxide is the most prevalent. Estimations indicate that up to 40% of greenhouse gases are emitted from the construction and building sector hence the urgency for climate change mitigation. The aim of this study was to determine the effectiveness of retrofitted certified green buildings of office use in the City of Johannesburg in terms of climate change mitigation during their operational lifecycle. The study utilized semi-structured interviews which were conducted with various stakeholders as well as existing literature. Their purpose was to gather the information needed to examine the various perspectives on green buildings in terms of climate change mitigation. Parallel to the human perceptions, energy consumption data was also collected from the property companies and meteorological data was collected from the South African Weather Services. These two data sets as well as calculated Carbon emission data were analysed against each other to examine whether climate, particularly temperature, impacted how buildings consume energy and emit Carbon emissions. The empirical evidence suggests that despite factors contributing to increased energy consumption and Carbon emissions in buildings existing, retrofitting and certifying existing office buildings in the City of Johannesburg generally mitigates this. The process of certification, like the majority of the legislation and institutional frameworks in existence countrywide governing green buildings, is voluntary and act more as a guide. Challenges in governance and implementation of legislation present an obstacle to realising the full potential of green buildings. Generally, the building sector in the country has been positively impacted by the green building phenomena with incentives from various economic sectors playing a significant role and other potential ones identified
A dissertation submitted in fulfilment of the requirements for the degree Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2021
Keywords: Climate change mitigation; Climatic changes